From Normal Flora to Brain Abscesses: A Review of Streptococcus intermedius - Issa, Elio; Salloum, Tamara; Tokajian, Sima (Frontiers in Microbiology, 2020)
Streptococcus intermedius is a β-hemolytic Gram-positive member of the Streptococcus anginosus group (SAG). Despite being a part of the normal microbiota, it is one of the most common pathogens associated with brain as well as liver abscesses and thoracic empyema increasing as a result the morbidity and mortality rates in affected patients. With numerous published case reports on S. intermedius infections, it is still understudied compared to other SAG members. Our knowledge of the genomic factors contributing to its dissemination to the brain and abscess development is also limited to few characterized genes. In this review, we summarize our current knowledge on S. intermedius identification methods, virulence factors and whole-genome provided insights and correlate patients’ metadata, symptoms and disease outcome with S. intermedius infections in 103 recent case reports obtained from PubMed. This combined information highlights the gaps in our understanding of S. intermedius pathogenesis suggesting future research directions to unveil the factors contributing to abscess development.